Implementing Project-Based Learning (PBL) Learning Course in ESP Classroom - Muhammad Mujtaba Mitra Zuana (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2016)
Some studies have been conducted concerning the use of project based learning (PBL) in language teaching and learning. Besides, those studies have been fruitful for explaining the benefits of PBL, it is also in compliance with the 21st century era where the digital technology influences the young generation to be more creative. That is why the use of PBL in Indonesia today is urgently need to facilitate students to develop their creativity. However, to implement PBL in teaching and learning process cannot be applied freely since every single subject has distinct characteristic. The methodology used in the class is one the crucial issues to determine the successfulness of implementing PBL in the classroom. These can be happened in English for specific purposes (ESP) speaking class which the characteristic of the learning process is technical English skill. Hence, this paper will present how to implement PBL appropriately accordance with the need of ESP speaking class in which the method develops students to have useful research and study skill, such as the use of reference resources and modern technology which are beneficial for learning. The implementation of PBL in ESP classroom will guide to the high English proficiency in some areas especially speaking skill